2006
DOI: 10.1007/s00374-006-0135-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of clay content and acidity of soil on development of the earthworm Lumbricus rubellus and its population level consequences

Abstract: In this paper we report on the influence of clay content and acidity of soil on growth and reproduction of the epigeic earthworm species Lumbricus rubellus (Hoffm.), which is common in most temperate soils and abundant in grasslands. Growth, cocoon production and survival of L. rubellus were tested in 12 Dutch soils which differed in soil properties. A matrix model was used to assess the population-level consequences of changes in growth and reproduction. Soil acidity had a strong negative effect on earthworm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 23 publications
2
6
0
2
Order By: Relevance
“…Since similar worm biomass existed in both treatments, it is clear that high clay contents have had a negative effect on worm activity that interfered with the formation of stable organomineral associations. This hypothesis is supported by the results of Klok et al (2007), who showed that Lumbricus rubellus worms can have their life cycle influenced by a high content of clay in soil, leading to anaerobic conditions and soil compaction. Given that species of the genus Eisenia (fetida and andrei) belong to the epigenic worm species living at the soil surface in leaf litter, they might not be well adapted to process high amounts of minerals.…”
Section: 2supporting
confidence: 75%
“…Since similar worm biomass existed in both treatments, it is clear that high clay contents have had a negative effect on worm activity that interfered with the formation of stable organomineral associations. This hypothesis is supported by the results of Klok et al (2007), who showed that Lumbricus rubellus worms can have their life cycle influenced by a high content of clay in soil, leading to anaerobic conditions and soil compaction. Given that species of the genus Eisenia (fetida and andrei) belong to the epigenic worm species living at the soil surface in leaf litter, they might not be well adapted to process high amounts of minerals.…”
Section: 2supporting
confidence: 75%
“…Second, the intrinsic physico-chemical characteristics of the soil-such as pH, salinity, texture and organic matter content-are known to affect metal uptake by earthworms (Ma et al, 1983;Owojori et al, 2008Owojori et al, , 2009aSpurgeon et al, 2006). Finally, distribution of earthworm populations is known to be affected by soil organic matter (Fonte et al, 2009;Jordan et al, 1999;Leroy et al, 2008;Monroy et al, 2011), salinity (Valckx et al, 2009), texture (Holmstrup et al, 2011;Klok et al, 2007), and pH (Klok et al, 2007); however, less attention has been paid on the effects of soil chemical and physical properties on earthworm responses in bioassays.…”
Section: Introductionmentioning
confidence: 97%
“…From an engineering perspective, clay content influences soil strength, permeability and consolidation (Al‐Shayea, ; Tembe et al , ). Clay content is also linked to soil biological activity, substrate availability and soil respiration (Wang et al , ; Klok et al , ).…”
Section: Introductionmentioning
confidence: 99%